(untitled) (INNOVATIVE ECONOMY, 2025)
Balaniuk I.F., Ivanochko B.R., Kuzmin T.L., Melnyk I.O. THE ESSENCE OF ECONOMIC CONTROL AND ITS PLACE IN BUSINESS ACCOUNTING AND ANALYTICAL SYSTEMS IN THE CONDITIONS OF DIGITAL TRANSFORMATION Purpose. The aim of the article is to theoretically generalize the essence of economic control, form its holistic scientific definition, and substantiate its place in the system of accounting and analytical support of an enterprise, taking into account the influence of digital technologies. Methodology of research. A set of methods that allowed us to comprehensively investigate the essence of economic control and substantiate its role in the system of accounting and analytical support of an enterprise, taking into account digital technologies were used in the article. Theoretical generalization and analysis of scientific sources were used to systematize approaches to the definition of economic control, types of control over business and their functional features. The systematic approach allowed us to consider economic control as a generalized category that unites different types of control, and to reveal the relationship between them as part of the system of accounting and analytical support of a business. Comparison and classification methods were used to highlight the main types of control and determine their role in verifying the compliance of the enterprise’s activities with economic goals, the efficiency of resource use and the performance of social and ethical functions. Analytical and logical methods ensured the formation of a holistic scientific definition of economic control, as well as the generalization of the capabilities of digital technologies in increasing its efficiency. The use of inductive and deductive approaches allowed us to combine general principles of control with specific digitalization tools, such as ERP systems, interactive analytical dashboards, electronic audit, analytical platforms and artificial intelligence, and to show their application in the practical activities of the enterprise. Thus, the chosen research methodology provided a comprehensive theoretical analysis of economic control and its digital tools, which is the basis for further practical recommendations on increasing the efficiency of accounting and analytical support systems for business. Findings. The study theoretically summarized the essence of economic control and proposed its holistic definition as a generalized category of all types of business control. It is shown that economic control integrates the functions of primary economic, managerial, internal, financial, external and social control, ensuring verification of the compliance of the enterprise’s activities with its economic goals, effective use of resources and the fulfilment of social and ethical functions. The study also identified the role of modern digital technologies in increasing the efficiency of economic control. Key digital tools are identified – ERP systems, interactive analytical dashboards, electronic audit, electronic document management, analytical platforms and artificial intelligence – and their capabilities in providing analytical assessment of the enterprise’s activities, monitoring business processes and integrating internal and external data for making informed management decisions are described. Originality. The scientific novelty of the obtained results lies in the systematization and generalization of approaches to the definition of economic control, the proposed holistic interpretation of the term "economic control", as well as in the study of the impact of digital technologies on increasing the analytical component and efficiency of control in the system of accounting and analytical support of the enterprise. Practical value. The practical significance is manifested in the identification of specific digital tools and methods of their use for economic control, which allows to increase the accuracy, efficiency and comprehensiveness of assessing the activities of the enterprise and making informed management decisions. Key words: economic control, accounting and analytical support, business, digital technologies, analytics, entrepreneurial activity.